O belo e o bom na "Vida capixaba" (1923-1933) : impressos e sensibilidades - Rocha, Luciane Paraiso (2018)
In this thesis we outline the following objectives: (i) to examine Vida Capichaba Magazine as a print intended to modify the ways of thinking and living of the capixabas - people from the State of Espírito Santo, Brazil, by forming a modern education of the sensitive; (ii) to analyze the representations of beautiful and good in Vida Capichaba Magazine in the period ranging from 1923 to 1933; and (iii) to understand in Vida CapichabaMagazine the commitment of its editors and collaborators to the use of a wide range of resources (textual, typographic, imagery), and distinct strategies aiming to modify representations about civility and sensitivities. We start from the assumption that the press founded in the republican period exerted enormous influence on the capixaba population so as to adopt new forms of life, pointing to the formation of sensibilities regarding spaces of the city in transformation. Our working hypothesis highlights Vida Capichaba Magazine as a spreader of ideas about good manners, civility and sensibilities created by a group of intellectuals who intended to modify the ways of thinking and living of the Capixabapopulation amidst the transformations of the early twentieth century. In this sense, we base the study on the concepts of representation by Roger Chartier (1990, 2002). In order to understand sensibilities, we need Lucien Febvre (1989), Pesavento (2003, 2005, 2007), Gay (1998), and the modern from Le Goff (2000) and Velloso (2010). The results emphasize the magazine as a transmitter of ideas and ideals that managed to influence the Capixabapopulation to modern sensibilities, by using texts and images aboutthe territory, about the orderly people, and behaviors expected in this society, adapting to the modern ideal of the early twentieth century.